Pulmonary Function and Respiratory Muscle Strength in Patients with Multiple Sclerosis - Westerdahl, Elisabeth; Gunnarsson, Martin; Wittrin, Anna; Nilsagård, Ylva (Multiple sclerosis international, 2021)
Background. In patients with multiple sclerosis (MS), there is a decline in muscle strength and physical capacity due to demyelination and axonal loss in the central nervous system. In patients with advanced MS or in a later stage of the disease, also respiratory impairment may occur. The degree of pulmonary dysfunction in the earlier stages of MS has not been thoroughly described. Therefore, the primary aims of this study are to describe pulmonary function and respiratory muscle strength in patients with a moderate disease course and to identify associations between respiratory muscle strength and functional capacity. Methods. A sample of 48 patients with a diagnosis of MS and mean age 56±11 years was studied using a descriptive cross-sectional design. The patients had a disease duration of 24±11 years and a median Expanded Disability Status Scale (EDSS) score of 4.5 (interquartile range 4.0-6.5). Pulmonary function assessed by spirometry, respiratory muscle strength, peak cough flow and peripheral oxygen saturation, subjective breathing and coughing ability, and physical capacity measured using the 6MWT were evaluated. Results. The patients had normal pulmonary function with no significant abnormalities in dynamic spirometry (vital capacity 103±16% predicted, forced expiratory volume in 1 second 95±15% predicted). Peak expiratory flow rate 89±17% predicted was in the lower limit of normal. Respiratory muscle strength, determined by maximal inspiratory (MIP) and expiratory (MEP) static pressures, was normal but with large differences between individuals. MIP ranged from 26 to 143 cmH2O (98±31% predicted); the MEP values ranged from 43 to 166 cmH2O (104±29% predicted), with two patients having values below the lower limit of normal. Significant positive associations between MIP as well as MEP were found in several pulmonary function variables. A significant negative association was found between EDSS score and MEP (r=−0.312, p=0.031). Mean peak cough flow was 389±70 L/min, which is comparable with the values reported for healthy adults. The patients did not experience a severely decreased ability to take deep breaths or cough. There was a moderate correlation between MEP and physical capacity, as assessed by the 6MWT (r=0.399, p=0.010) and between peak expiratory flow (PEF) and the 6MWT (r=0.311, p=0.048). Conclusion. Respiratory muscle strength, pulmonary function assessed by spirometry, and peak cough flow were normal in patients with mild to moderate MS; however, there were large individual differences demonstrating low respiratory muscle strength in some patients. Significant associations between MEP and functional capacity and between MEP and disease severity were found, indicating that patients with impaired respiratory muscle strength have lower functional capacity and more severe disease.